The Influence Of Event Marketing, Influencer And E-Wom On Purchase Intention Skin Mobile Legends In Malang Town - Angelysander Altair; Stefanus Yufra Menahen Taneo; Santi Widyaningrum (Brilliant International Journal Of Management And Tourism, 2024)
Based on Moonton's data, the monthly active players of Mobile Legends in Indonesia, totaling 34 million, are predominantly from Java and Sumatra. About 52 percent of Mobile Legends players come from Java Island, while 29.38 percent come from Sumatra Island. The distribution on other islands includes Kalimantan (7.41 percent), Sulawesi (6.29 percent), Bali (3.73 percent), and Papua (0.54 percent). The purpose of this research is to determine and analyze the influence of event marketing, influencer marketing, and electronic word-of-mouth (e-wom) on the purchase intention of Mobile Legends skins in Malang City. The research method employed in this study is quantitative. The population in this research consists of all Mobile Legends players in Malang City. The sample for this research consists of 100 individuals selected through accidental sampling technique. Data collection in this research is done using a questionnaire. Data analysis techniques in this research include Multiple Linear Regression Analysis, Hypothesis Testing (t-test & f-test), and the Coefficient of Determination. Data processing in this research is conducted using SPSS (Statistical Package for the Social Sciences) version 25 software. The results of this research prove that Event Marketing, Influencer Marketing, and E-WOM collectively influence the Purchase Intention of Mobile Legends skins.